An Ink‐Composition Engineering Approach for Upscaling of Organic Solar Cells with High‐Efficiency Retention Factor. Issue 10 (23rd July 2020) - Andersen, Thomas R.; Zhao, Feng; Li, Yaokai; Dickinson, Michael; Chen, Hongzheng
Abstract : The potential for commercialization of organic solar cells (OSCs) has vastly increased in recent years as the device efficiency for small‐scale laboratory OSCs has continuously increased. There are, however, still multiple challenges that need to be addressed and overcome. Among them, upscaling of the device manufacturing techniques to be compatible with the potential attributes of low cost must be the pinnacle. Herein, a pathway for upscaling with an ink‐engineering approach toward in‐air optimization of large‐area OSCs is presented. Optimized flexible indium tin oxide (ITO)‐free OSCs based on a PTB7‐TH:IEICO‐4F:PC71 BM ternary blend show efficiencies up to 10.2% (device active area 0.88 cm 2 ), which is the highest value reported to date (for in‐air slot‐die‐coated devices). This is achieved through ink modifications and optimizations as well as electrode and active layer compositional optimizations, leading to an impressive efficiency retention of 0.86 compared to the in‐literature optimized small‐scale devices. Abstract : Herein, an ink‐composition engineering approach for high‐performing flexible slot‐die‐coated indium tin oxide (ITO)‐free organic solar cells is presented. Optimized large‐area devices (0.88 cm 2 ) show a power conversion efficiency of up to 10.21%, which is an efficiency retention factor of 0.86 when compared to optimized small‐area spin‐coated devices.